Pertanggungjawaban Hukum Badan Pertanahan Nasional Terhadap Penerbitan Sertifikat Ganda - Nifantri Mulya Ningsih; Marthinus Johanes Saptenno; Sherlock Halmes Lekipiouw (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction:  The issuance of dual certificates, namely certificates of more than one ownership in the same land area. As a result of the issuance of double certificates, there is a dispute between the parties.Purposes of the Research: To find out the form of the responsibility of the national land agency for the issuance of multiple certificates and their legalMethods of the Research: The research is a normative legal research in the study using two problem approach and the conceptual approach. Sources of data obtained are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is by collecting and grouping them according to their respective sections, both primary, secondary and tertiary laws. the whole data in this stuidy was analyzed qualitatively. Results of the Research: The results of this study indicate that the national land agency is responsible fir the certificates issued releted to the with the head of the national land agency. the national land  agency is absolutely responsible for the issuance of multiple certificates as a result of negligence due to the inaccuracy of the national land agency. the absolute responsibility system requires the national land agency to be responsible both inside and outside the court if there is a lawsuit regarding land rights. the legal consequence of the issuance of multiple certificates issuedvy the national land agency is to create legal uncertainty because there is more than one certyificates in the same parcel of land, losses for the both parties to the dispute, especially for those who are declared defeated in the trial and certificates that are proven administratively dlawed or inten tionally registered return.